"Finding home": Affective geographies of regional youth (im)mobilities. Issue 1 (13th October 2021) - Boyd, Candice P.; Harada, Theresa
Abstract: In this paper, we aim to contribute to a growing body of literature that explores the affective geographies of young people's internal migration decisions using mobilities/immobilities as our conceptual framework. As such, our focus is not only on why young people choose to leave their hometowns but also why some choose to stay. By paying attention to young people's experiences of being away, we also shed light on why some young people choose to return to regional areas having left for a time. In emphasising the affective, material, and embodied dimensions of these experiences, the affordances of rural and urban places are also brought to light. Fifty young people aged between 18 and 34 years from three regional Australian towns took part in the study by participating in semi‐structured interviews. Qualitative findings indicate that the internal migration decisions of these regional young people were predominantly affective. We demonstrate how bodies were affected by the particularities of place – including materialities and relations with human and non‐humans – that worked to connect or unify bodies, evoking feelings of inclusion and security. We discuss how the affective atmospheres of places pushed into and onto bodies, making them feel dislocated or oppressed, and the way that places worked to push bodies out through the embodied experience of difference. The participants in our study emphasised the dilemma of these affective pushes and pulls, where feelings of belonging, or longing for home or country had to be negotiated, reconsidered, and re‐worked in relation to the unfolding of place. Abstract : Fifty young people from three regional Australian towns took part in semi‐structured interviews about their internal migration decisions. Findings revealed the affective, material, and embodied dimensions of their migration decisions and experiences.